8(x+5)+3(x+5)=x-6

Simple and best practice solution for 8(x+5)+3(x+5)=x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(x+5)+3(x+5)=x-6 equation:


Simplifying
8(x + 5) + 3(x + 5) = x + -6

Reorder the terms:
8(5 + x) + 3(x + 5) = x + -6
(5 * 8 + x * 8) + 3(x + 5) = x + -6
(40 + 8x) + 3(x + 5) = x + -6

Reorder the terms:
40 + 8x + 3(5 + x) = x + -6
40 + 8x + (5 * 3 + x * 3) = x + -6
40 + 8x + (15 + 3x) = x + -6

Reorder the terms:
40 + 15 + 8x + 3x = x + -6

Combine like terms: 40 + 15 = 55
55 + 8x + 3x = x + -6

Combine like terms: 8x + 3x = 11x
55 + 11x = x + -6

Reorder the terms:
55 + 11x = -6 + x

Solving
55 + 11x = -6 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
55 + 11x + -1x = -6 + x + -1x

Combine like terms: 11x + -1x = 10x
55 + 10x = -6 + x + -1x

Combine like terms: x + -1x = 0
55 + 10x = -6 + 0
55 + 10x = -6

Add '-55' to each side of the equation.
55 + -55 + 10x = -6 + -55

Combine like terms: 55 + -55 = 0
0 + 10x = -6 + -55
10x = -6 + -55

Combine like terms: -6 + -55 = -61
10x = -61

Divide each side by '10'.
x = -6.1

Simplifying
x = -6.1

See similar equations:

| 35=-5/8u | | x+.06x=10 | | 81x^2-7=93 | | 5(x+4)+6=-4 | | 8v-3v=-19-11 | | x+.6x=10 | | -26=2n | | 81x^2-7=94 | | 3y=-5.1 | | 7t-t-4=5t-6 | | 2t^2=9+t^2 | | 11x+42=7x-12 | | W^2=4w-3 | | 10x-4=12x | | x-0.3=42 | | 7(7c+1)-4c=13c(3c-2) | | 5x-7=3y | | 4/5w-1/5x=-7/3-7/3 | | 5x^2-x=3x+2 | | 3+4(x+1)=158 | | 4x^2-15x=18 | | y=e-1 | | 4y=-3.6 | | F(x)=2x+x^2+3(4c)+17 | | log(y)=5t+2 | | 5/8t=4 | | 12e=-12 | | (2x-3)(x+4)=(x-6)(x+2) | | 6x+60=100 | | logx+log(3x-130)=1 | | 4(-2)-3y=18 | | 6x+60=480 |

Equations solver categories